Driving through floodwater: Exploring driver decisions through the lived experience. (March 2019) - Hamilton, Kyra; Peden, Amy E.; Keech, Jacob J.; Hagger, Martin S.
Abstract: More than half of unintentional flood-related drowning deaths in Australia are due to driving through floodwater, despite on-going public campaigns. Currently, there is a knowledge gap in understanding why individuals choose to drive through floodwater and the decisions that may lead to such actions. We propose that a more complete understanding of individuals' decisions to drive through floodwater needs to be considered in the context of the lived experience. Australian drivers (N = 20) who had intentionally driven through floodwater participated in semi-structured interviews. Data were analysed using a thematic analysis based in an interpretivist approach. Past experience, individual perceptions (e.g., situation perceived as different to warnings), and the social and environmental context (e.g., pressure and encouragement from others, seeing other motorists driving through) emerged as major themes. Most salient was that although there was a common awareness of the risk posed by driving through flooded waterways, the decision to take this risk emerged as being heavily reliant on one's ability to construct a sense of self-efficacy in the lead-up to the incident. This study is the first to explore the lived experience of drivers who intentionally decided to drive through floodwater. Future research and public campaigns can draw on these findings to develop evidence-based interventions aimed at combating this risky driving behaviour.